Neurocognitive Performance of 425 Top-Level Football Players: Sport-specific Norm Values and Implications. (25th August 2018) - Prien, Annika; Junge, Astrid; Brugger, Peter; Straumann, Dominik; Feddermann-Demont, Nina
Abstract: Objective: Concussion diagnosis and management in sports largely relies on neurocognitive testing. In the absence of baseline assessment, only norm values of the general population are available for comparison with scores of concussed athletes. To evaluate whether (elite) sport specific norm values are needed, cognitive performance was compared between top-level football players and the general population. Methods: Cognitive performance of 425 top-level football players was evaluated using the computerized test battery CNS Vital Signs. Players were split into two age groups (15–19 and 20–29 years) and test results were compared with a norm sample ( n = 268) by means of age-standardized scores using Cohen's d effect size statistics. Results: The younger age group outperformed the norm sample in all domains, with small to moderate effects on tests of processing speed ( d = 0.58, 95% CI = 0.31, 0.85), cognitive flexibility ( d = 0.27, 95% CI = 0.01, 0.53) and psychomotor speed ( d = 0.97, 95% CI = 0.69, 1.24). In the older age group, no differences were found on four out of six domains; a moderate positive effect was found for psychomotor speed ( d = 0.74, 95% CI = 0.54, 0.93), a small negative effect for reaction time ( d = −0.47, 95% CI = −0.66, −0.28). Relative to the norm, older football players scored lower than younger football players on all test domains. Conclusion: Cognitive performance of elite football players may be different from the general population. It is recommended to use football-specific norm scores for comparison with test results of concussed players, and to choose an adequate control group when investigating effects of contact sport on cognition. Studies with older/retired football players are needed to further analyze potential sport-specific age effects.